2023
DOI: 10.3390/su151310516
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ecological Benefits of Urban Green Spaces in Nanjing City, China, Based on the Entropy Method and the Coupling Harmonious Degree Model

Abstract: Urban green spaces (UGSs) are an important spatial carrier for carbon sequestration in the national land space. The urban ecosystem is a highly harmonious composite ecosystem of nature, society, and the economy. Therefore, this study constructed an evaluation system of the UGS ecological benefit based on two subsystems–the natural environment and the social economy–in order to quantitatively evaluate the construction level of the UGS ecological benefit in Nanjing City and to reveal its temporal evolution chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Additionally, we found that the Porter diamond model (Porter, 1990) and the Shannon entropy (Shannon, 1948) can be used to construct the CCI index. Although the Shannon entropy is often used to compute composite indices in economics and management (Ji et al , 2023; Karagiannis and Karagiannis, 2019), this is the first time that it is used to compute the CCI index. The difficulty of constructing the CCI index may be one of the reasons that few studies assessed CCIs’ contributions quantitatively at the regional level.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that the Porter diamond model (Porter, 1990) and the Shannon entropy (Shannon, 1948) can be used to construct the CCI index. Although the Shannon entropy is often used to compute composite indices in economics and management (Ji et al , 2023; Karagiannis and Karagiannis, 2019), this is the first time that it is used to compute the CCI index. The difficulty of constructing the CCI index may be one of the reasons that few studies assessed CCIs’ contributions quantitatively at the regional level.…”
Section: Discussionmentioning
confidence: 99%
“…The Nanjing Municipal Government has implemented a series of progressive environmental protection policies and measures, such as the "13th Five-Year Plan for Ecological Environment Protection in Nanjing" (2016) and the "Nanjing Environmental Protection Regulations" (2017). As a result, the quality of the ecological environment in Nanjing has consistently improved over the years [53]. However, unlike other air pollutants, concentrations of O 3 increased.…”
Section: Temporal Variation Patterns Of Air Pollutants In Nanjingmentioning
confidence: 99%
“…Nanjing City is situated in eastern China, at the lower reaches of the Yangtze River (31 • 14 N-32 • 37 N, 118 • 22 E-119 • 14 E). It is geographically located in a narrow northsouth and east-west direction [29]. The southern part of the city features low mountains, hills, river valleys, lakeside plains, and riverbanks, collectively forming a diverse landform system.…”
Section: Study Areamentioning
confidence: 99%